2021
DOI: 10.1111/inm.12947
|View full text |Cite
|
Sign up to set email alerts
|

What should be the future focus of mental health nursing? Exploring the perspectives of mental health nurses, consumers, and allied health staff

Abstract: The landscape of mental health care and service delivery is changing, as is our understanding of the underlying causes for mental distress. It is now apparent that biogenic explanations have been overstated and instead experiences of trauma and adversity constitute the main contributor to people's experiences of mental health challenges. The shortcomings of treatments traditionally used in mental health care are also evident, and with a contemporary focus on person-centred care, the utility of diagnostic label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 67 publications
0
29
0
5
Order By: Relevance
“…There is no undisputed definition of mental health nursing (Barker & Buchanan-Barker 2011) outside of the pragmatic position of holding a named specialist qualification in it (Australian College of Mental Health Nursing 2010). Having roots in the asylum model of care, MHN roles are often seen as primarily custodial, basic, and under their practice under the direction of medicine (Wand et al 2021). Despite the move to community models of mental health service provision some 40 years ago, the bulk of MHN workforce remains confined to in-patient settings (Australian Institute of Health & Welfare 2021).…”
Section: Clarification Of the Role And Identity Of The Mhnmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no undisputed definition of mental health nursing (Barker & Buchanan-Barker 2011) outside of the pragmatic position of holding a named specialist qualification in it (Australian College of Mental Health Nursing 2010). Having roots in the asylum model of care, MHN roles are often seen as primarily custodial, basic, and under their practice under the direction of medicine (Wand et al 2021). Despite the move to community models of mental health service provision some 40 years ago, the bulk of MHN workforce remains confined to in-patient settings (Australian Institute of Health & Welfare 2021).…”
Section: Clarification Of the Role And Identity Of The Mhnmentioning
confidence: 99%
“…Having roots in the asylum model of care, MHN roles are often seen as primarily custodial, basic, and under their practice under the direction of medicine (Wand et al . 2021 ). Despite the move to community models of mental health service provision some 40 years ago, the bulk of MHN workforce remains confined to in‐patient settings (Australian Institute of Health & Welfare 2021 ).…”
Section: Background: Scope Of the Challengesmentioning
confidence: 99%
“…There might also be implications for the Ugandan community at large. Health education and health promotion have been identified as key roles in the profession [ 39 ]. That nurses have a responsibility as role models for the community is questioned by some [ 40 ], but there is little challenge to the presumption that health professionals´ behaviors are an influence on the population [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Related research, while not specifically focused on hope, has also provided some information about the hope-supporting practices used by mental health workers. For example, in studies of desirable characteristics of health professionals, people who access services have described the following features as inspiring hope: collaborative working, treating them as equals, optimism, and belief in their ability to recover (Horgan et al, 2021 ; Wand et al, 2022 ). A recent meta-synthesis of Norwegian literature on recovery-oriented practices (Klevan et al, 2021 ) identified that to promote hope, practitioners needed to help people to believe in themselves and others and to help people to see and acknowledge future opportunities.…”
Section: Introductionmentioning
confidence: 99%